Economic policy and unemployment in Russia's regions - Tatiana Blinova; Victor Rusanovsky (European Regional Science Association (ERSA), 2002)
Theoretical and empirical analysis of the regional labor market differences and the factor making them exist enabled to assess the structural imbalance in the Russia's transition economy. By making cluster and discriminant analyses, the authors provide alternative classifications of the regions and estimate the impact of such specific regional factors as structure of industry employment and economic policy on regional level on the labor markets performances behavior. The transition Russian economy gave birth to a regionally segmented labor market model with the inefficient structure of industry employment. In the suggested theoretical model the regions, first, have different starting conditions for the labor market and, second, pursue their economic policies in a different way. Economic policies on the regional level include privatization and promotion of private ownership, small and medium sized firms, local infrastructures and investments in human capital. The industrial structure is being formed over a long period of time and depends on the state strategy of placement of production around the territory of the country. Institutional structure of employment much depends on the economic policy of the region and on the rate of development of small business, private sector, enterprises with foreign participation, infrastructure and on the amount of investments in the human capital. If the economic policy implemented in the region has the aim to increase the efficiency of the institutional structure of employment, the risk of unemployment tends to be lower. At the same time if the private sector, the infrastructure, small business and education are underdeveloped, the risk of unemployment in that region is high. Consequently, unfavorable starting conditions for a labor market and inefficiency of the structure of industry employment can be to a certain extent offset by a regional economic policy intended to promote the non-state sector, small and medium sized firms, regional infrastructure and investments in human capital.
Keywords: 330